IDEOLOGICAL AND IDEOLOGICAL FACTORS INFLUENCING THE FORMATION OF PROFESSIONAL CULTURE OF MODERN LEADERS - Ikramjon Batirovich Masharipov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, the moral conditions affecting the professional culture of modern leaders and the factors influencing it are determined. In order to achieve this goal, it is necessary to optimize the process of spiritual development of the leaders who meet the requirements of the present time, to think about the social, ideological and ideological factors affecting their activities. Social conditions in most cases become objective for the subject of work, and most of the ideological and ideological factors have a subjective nature. comments on the improvement of the objective conditions related to the current professional activity system and the objective-subjective conditions related to the structure of the professional environment and the subjective factors related to the individual foundations of the level of effectiveness of spiritual development of the spiritual aspect of professional culture were formed.